ANALISIS WACANA IKLAN ROKOK SAMPOERNA MILD - Puspita Dewi; Sulmi Magfirah (LPPM Universitas Bumigora Mataram, 2018)
Mass media is one of the great services utilized by people who have the purpose of selling goods and providing services to the public. Mass media is the right market to promote an item or service so that choosing the right diction is a must. The purpose of this study is to identify the meaning of the sentence in the Sampoerna Mild cigarette advertisement